2013
DOI: 10.1371/journal.pone.0057880
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Disturbed Eating Behavior and Socioeconomic Status: The Online Korean Adolescent Panel Survey (OnKAPS)

Abstract: BackgroundA limited amount of research, primarily conducted in Western countries, has suggested that higher socioeconomic status (SES) is associated with higher risk of eating disorders (EDs). However, little is known about this association in Asian countries. We examined the association of SES with disturbed eating behavior (DEB) and related factors in Korean adolescents.SubjectsA nationwide online panel survey was conducted in a sample of adolescents (n = 6,943, 49.9% girls). DEB was measured with the 26-ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 35 publications
5
20
0
2
Order By: Relevance
“…Our analysis found overall 6.2% of prevalence of DWCB among Korean adolescents (9.0% of girls and 3.7% of boys), consistent with a previous study (Lee et al, ), showing that the ratios of the prevalence of DWCB between Korean and U.S. adolescents (i.e., 16.7% among 9th–12th graders from the YRBSS) ranged 1:2.4 to 1:2.7. This aligns with findings from recent studies showing comparable prevalence of disordered eating behaviors (DEB), defined by the Korean translated EAT‐26 scores of 20 or above, among Korean adolescents (14.8% in girls and 10.5% in boys) to that among U.S. adolescents (14.4% in girls and 3.8% in boys) (Lee et al, ), greater level of body dissatisfaction among Korean young women than U.S. young women (Jung & Forbes, ), and substantial number of ED cases among Korean women (Kim et al, ). Moreover, our study adds to the current literature by documenting the prevalence of one‐food diet in Korean youth (overall 2.7%, girls 4.0%, boys 1.5%), which may be a Korea‐specific DWCB.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our analysis found overall 6.2% of prevalence of DWCB among Korean adolescents (9.0% of girls and 3.7% of boys), consistent with a previous study (Lee et al, ), showing that the ratios of the prevalence of DWCB between Korean and U.S. adolescents (i.e., 16.7% among 9th–12th graders from the YRBSS) ranged 1:2.4 to 1:2.7. This aligns with findings from recent studies showing comparable prevalence of disordered eating behaviors (DEB), defined by the Korean translated EAT‐26 scores of 20 or above, among Korean adolescents (14.8% in girls and 10.5% in boys) to that among U.S. adolescents (14.4% in girls and 3.8% in boys) (Lee et al, ), greater level of body dissatisfaction among Korean young women than U.S. young women (Jung & Forbes, ), and substantial number of ED cases among Korean women (Kim et al, ). Moreover, our study adds to the current literature by documenting the prevalence of one‐food diet in Korean youth (overall 2.7%, girls 4.0%, boys 1.5%), which may be a Korea‐specific DWCB.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, recent studies have found that the preference toward thin body is the strongest in South Korea compared to all other countries participating in the worldwide Project Implicit (Marini et al, ) and the per capita cosmetic surgery rate was the highest in South Korea around the world in 2011, according to the International Society of Aesthetic Plastic Surgeons (Holliday & Elfving‐Hwang, ; You, Shin, & Kim, ). Relatedly, studies have found that the level of body dissatisfaction was greater among Korean young women than U.S. young women (Jung & Forbes, ) and the prevalence of disordered eating behavior, defined as the 26‐item Eating Attitude Test (EAT‐26) score of 20 or above, among South Korean adolescents (12.7%) was comparable to that among U.S. adolescents (14.4%) (Lee et al, ).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…13 However, a Korean study reported that the association between SES and risk of eating disorders among girls was U-shaped, with increased risk among those with either lowest or highest SES. 20 …”
Section: Introductionmentioning
confidence: 99%
“…A higher score indicates more abnormal eating attitudes and behaviors. In this study, scores of 20 or more indicated disturbed eating behavior [22,23]. The Cronbach's alpha of this test was 0.84.…”
Section: Eating Attitudesmentioning
confidence: 79%